Interactions of the Intracellular Bacterium Cardinium with Its Host, the House Dust Mite Dermatophagoides farinae, Based on Gene Expression Data - Hubert, Jan; Nesvorna, Marta; Klimov, Pavel B; Erban, Tomas; Sopko, Bruno; Dowd, Scot E; Scully, Erin D (mSystems, 2021)
Dermatophagoides farinae is inhabited by an intracellular bacterium, Cardinium. Using correlations between host and symbiont gene expression profiles, we identified several important molecular pathways that potentially regulate/facilitate their interactions. The expression of Cardinium genes collectively explained 95% of the variation in the expression of mite genes assigned to pathways for phagocytosis, apoptosis, the MAPK signaling cascade, endocytosis, the tumor necrosis factor (TNF) pathway, the transforming growth factor beta (TGF-β) pathway, lysozyme, and the Toll/Imd pathway. In addition, expression of mite genes explained 76% of the variability in Cardinium gene expression. In particular, the expression of the Cardinium genes encoding the signaling molecules BamD, LepA, SymE, and VirD4 was either positively or negatively correlated with the expression levels of mite genes involved in endocytosis, phagocytosis, and apoptosis. We also found that Cardinium possesses a complete biosynthetic pathway for lipoic acid and may provide lipoate, but not biotin, to mites. Cardinium gene expression collectively explained 84% of the variation in expression related to several core mite metabolic pathways, and, most notably, a negative correlation was observed between bacterial gene expression and expression of mite genes assigned to the glycolysis and citric acid cycle pathways. Furthermore, we showed that Cardinium gene expression is correlated with expression levels of genes associated with terpenoid backbone biosynthesis. This pathway is important for the synthesis of pheromones, thus providing an opportunity for Cardinium to influence mite reproductive behavior to facilitate transmission of the bacterium. Overall, our study provided correlational gene expression data that can be useful for future research on mite-Cardinium interactions. IMPORTANCE The molecular mechanisms of mite-symbiont interactions and their impacts on human health are largely unknown. Astigmatid mites, such as house dust and stored-product mites, are among the most significant allergen sources worldwide. Although mites themselves are the main allergen sources, recent studies have indicated that mite-associated microbiomes may have implications for allergen production and human health. The major medically important house dust mite, D. farinae, is known to harbor a highly abundant intracellular bacterium belonging to the genus Cardinium. Expression analysis of the mite and symbiont genes can identify key mite molecular pathways that facilitate interactions with this endosymbiont and possibly shed light on how this bacterium affects mite allergen production and physiology in general.
Keywords: interactions; endosymbiont; house dust mite; symbiont; Cardinium; transcriptome; allergens; host-pathogen interactions